The Balanced Scorecard Model: A Pattern of Performance management in Public sectors - seyed mehdi alvaani; mirali seyed naghavi (مطالعات مدیریت بهبود و تحول, 2016)
The Balanced scorecard is a measurement model that expected to over come some of the deficiencies of traditional performance techniques. It gives a holistic view of the organizations by simultaneously looking at four important prespectives (financial, customer, internal process, innovation and Learning). In this article; we reviewed the literature on the Balanced scorecard, it's origins and principles, strenghs and weaknesses. Finally, It has been said that the BSC could have many important applications in public Administration